Level of membrane-bound hemoglobin and red-cell membrane proteins in patients with essential hypertension complicated and not complicated with metabolic syndrome - Y. I. Pivovarov (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
We studied the effect of different levels of membrane-bound hemoglobin on the level of red-cell membrane proteins and also their interrelation in patients with essential hypertension with and without metabolic syndrome. It wasfound that high membrane-bound hemoglobin is closely related to the low level of high-density lipoproteins and high level of low-density lipoproteins in patients with essential hypertension complicated with metabolic syndrome. In patients with essential hypertension not complicated with metabolic syndrome high membrane-bound hemoglobin is related to the increased prothrombin time and decreased blood urea nitrogen. In patients with essential hypertension complicated with metabolic syndrome high membrane-bound hemoglobin significantly influences the level of membrane contractile proteins (actin, tropomiosine). In patients with essential hypertension without metabolic syndrome high membrane-bound hemoglobin is accompanied by the decrease of structural and integral membrane proteins levels (anion-transport protein and protein 4.1). As the result of quantitative changes in these proteins and change in their interrelations in patients with ssential hypertension complicated with metabolic syndrome more intensive disorders of structural and functional organization of red-cell membrane can appear.